Impact of Pituitary Stalk Preservation on Tumor Recurrence/Progression and Surgically Induced Endocrinopathy After Endoscopic Endonasal Resection of Suprasellar Craniopharyngiomas - Chen, Zhengyuan; Ma, Zengyi; He, Wenqiang; Shou, Xuefei; Ye, Zhao; Zhang, Yichao; Zhang, Qilin; Qiao, Nidan; Zhou, Xiang; Cao, Xiaoyun; He, Min; Zhang, Zhaoyun; et al. (Frontiers in Neurology, 2021)
[Objective]. To investigate the factors associated with recurrence/progression after endoscopic endonasal resection of suprasellar craniopharyngiomas. Special attention was paid to assess the impact of pituitary stalk preservation on tumor recurrence/progression and endocrinological outcomes. [Methods]. We retrospectively recruited 73 patients with suprasellar craniopharyngiomas undergone endoscopic endonasal approach (EEA) surgery from September 2014 to May 2019 and assessed their clinical characteristics, surgical outcomes, and recurrence/progression. Stalk preservation or sacrifice was determined by reviewing operative records, videos, and postoperative magnetic resonance imaging. [Results]. Gross total resection (GTR) was achieved in 51 cases (69.9%). Tumor recurrence was seen in 5 cases (9.8%) and progression was seen in 8 cases (36.4%), respectively. GTR (OR = 0.248 CI 0.081-0.759; p = 0.015) was the only independent factor influencing recurrence/progression. Kaplan-Meier survival analysis showed that the mean recurrence/progression-free survival were 53 (95% CI 48-59) and 39 (95% CI 28-50) months, respectively in patients with and without GTR (p = 0.011). Pituitary stalk preservation was more common in cases with peripheral type tumors (83% vs. 30%, p＜0.01). Preserving the pituitary stalk does not appear to decrease the percentage of GTR (75.5% vs. 55.0%, p = 0.089), or increase the rate of tumor recurrence (12.5% vs. 0%, p = 0.508) or progression (46.2% vs. 22.2%, p = 0.486). However, surgically induced hypothyroidism (60.5% vs. 100%, p = 0.041) and diabetes insipidus (35.1% vs. 81.8%, p = 0.017) were significantly lower in patients with stalk preservation. For patients who had hypopituitarism before EEA, there was no difference between those with and without stalk preservation regarding postoperative hypopituitarism (p > 0.05). [Conclusion]. GTR is the only independent predictor of recurrence/progression after EEA surgery for suprasellar craniopharyngiomas. Preserving the pituitary stalk does not appear to increase the risk of non-GTR and tumor recurrence/progression and might help reduce the risk of surgically induced hypothyroidism and diabetes insipidus. We recommend preserving the pituitary stalk in peripheral type suprasellar craniopharyngiomas with normal pituitary function, especially in cases without hypothyroidism or diabetes insipidus. On the other hand, stalk sacrifice could be considered in central type tumors with severe preoperative endocrinopathy.